1992
DOI: 10.1007/bf00040021
|View full text |Cite
|
Sign up to set email alerts
|

A revised scheme for mass propagation of Easter Lily

Abstract: Lilium longiflorum Thunb., commonly known as Easter Lily is widely propagated by vegetative means for its high ornamental value as a pot plant. Following in vitro technique, mass propagation has been achieved through direct production of bulblets from the explant as well as regeneration from callus. The chromosome analysis of the progeny derived from callus even from long term culture, did not reveal any marked variability in chromosome morphology. The stable nature of callus maintained in modified MS medium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 9 publications
(9 reference statements)
2
9
0
Order By: Relevance
“…Next, it requires the formation of the embryo proper, which is achieved upon transfer of the embryogenic cells to the hormone-free medium (here, lily regeneration through these procedures). A number of laboratories have already reported the regeneration of lily plants through organogenesis (Stimart and Ascher 1978;Liu and Burger 1986;Priyadarshi and Sen 1992;ArzateFernandez et al 1997;Nhut 1998), while regeneration of lilies through somatic embryogenesis has also been reported (Tribulato et al 1997;Nakano et al 2000). Tribulato et al (1997) confirmed the bipolarity of regenerants by histological investigation of the differentiation process in Lilium longiflorum.…”
Section: Plant Regenerationsupporting
confidence: 66%
“…Next, it requires the formation of the embryo proper, which is achieved upon transfer of the embryogenic cells to the hormone-free medium (here, lily regeneration through these procedures). A number of laboratories have already reported the regeneration of lily plants through organogenesis (Stimart and Ascher 1978;Liu and Burger 1986;Priyadarshi and Sen 1992;ArzateFernandez et al 1997;Nhut 1998), while regeneration of lilies through somatic embryogenesis has also been reported (Tribulato et al 1997;Nakano et al 2000). Tribulato et al (1997) confirmed the bipolarity of regenerants by histological investigation of the differentiation process in Lilium longiflorum.…”
Section: Plant Regenerationsupporting
confidence: 66%
“…1). This method is however, considered to be a low-risk method for genetic instability (Takayama and Misawa, 1983;Priyadarshi and Sen, 1992). Further, screening of these in vitro-raised bulblets was done to establish clonal fidelity using RAPD markers.…”
Section: Resultsmentioning
confidence: 99%
“…Lilium species in particular can be efficiently multiplied by bulblet formation or by somatic embryogenesis (Priyadarshi and Sen, 1992;Niimi et al, 1997;Pelkonen, 1997;Chang et al, 2000). Alternatively, leafy bulb scales regeneration from scale a Data were scored after 6 weeks of culture; b Data followed by different letters are significantly different (P<0.05); c On hormone-free MS medium, the mean number of bulblets per explant was 2.61 ± 0.50 (with leaves 0.06 ± 0.04).…”
Section: Discussionmentioning
confidence: 99%